Capital Adequacy Ratio dan Beban Operasional Terhadap Profitabilitas Pada Bank Umum Syariah - Resti Purwita Sari; Tupi Setyowati (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2017)
This study aims to analyze and determine the effect of Capital Adequacy Ratio (CAR), Operating Cost Operating Income (BOPO) to Profitability proxyed using Return On Assets (ROA) at Sharia Commercial Bank in Indonesia period 2014-2015. This research uses data source secondary documentation of the annual financial statements of Sharia Commercial Banks in Indonesia and supplemented by other bibliographic data sources. The result of the research shows that Capital Adequacy Ratio (CAR) has negative and insignificant effect on Return On Asset (ROA) at Sharia Commercial Bank in Indonesia and Operating Cost Operating Income (BOPO) have negative and significant effect to Return On Asset (ROA) at Sharia Commercial Bank in Indonesia